COMPARATIVE ANALYSIS OF STOCK TRADING VOLUME BEFORE AND AFTER CONDUCTING STOCK SPLIT ON COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2014-2016 - Indrayani Indrayani; Murhaban Murhaban; Syatriani Syatriani (Universitas Airlangga, 2020)
This study aims to analyze the comparison of the trading volume of shares before and after a stock split on companies listed on the Indonesia stock exchange in 2014-2016. This study uses secondary data in the form of annual financial statements of manufacturing companies in the Indonesia stock exchange in 2014-2016. The number of samples in this study is 30 companies selected using Purposive sampling techniques based on certain criteria. Data analysis methods used in this study are descriptive statistical methods and normality tests. Based on the results of hypothesis testing conducted, it shows that there are differences in the volume of stock trading before and after a stock split on companies listed on the Indonesia Stock Exchange in 2014-2016.